Electrical double layer capacitor using poly(methyl methacrylate)-C4BO8Li gel polymer electrolyte and carbonaceous material from shells of mata kucing (Dimocarpus Longan) fruit - Arof, Abdul Kariem; Kufian, M.Z.; Syukur, M.F.; Aziz, M.F.; Abdelrahman, A.E.; Majid, Siti Rohana (Elsevier, 2012)
Poly(methyl methacrylate), PMMA based gel polymer electrolytes (GPE) containing immobilized lithium bis(oxalato)borate, C4BO8Li or LiBOB dissolved in a propylene carbonate-ethylene carbonate binary solvent were prepared by heating the cast solution between 70 and 80 degrees C for 20 min. The electrolyte composition with 5 wt.% PMMA exhibited the highest conductivity of 3.27 and 7.46 mS cm(-1) at 298 and 343 K respectively. Cyclic voltammetry studies on the GPE containing 15 wt.% PMMA and 85 wt.% (0.6 M LiBOB) dissolved in equal weight of ethylene and propylene carbonates showed that the electrochemical potential stability window of the electrolyte lies in the range between -1.7 to +1.7 V. Linear sweep voltammetry indicates the gel polymer electrolyte is stable up to 1.7 V. The electrical double layer capacitor (EDLC) using the highest conducting GPE and activated carbon derived from shells of the mata kucing (Dimocarpus longan) fruit has capacitance of similar to 685 mF g(-1) on the first cycle. The EDLC performance was also characterized using cyclic voltammetry and charge-discharge processes at constant current. (C) 2012 Elsevier Ltd. All rights reserved.